José Emilio Pacheco Translating Samuel Beckett. The case of Cómo es (1966) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The first translation into Spanish of Samuel Beckett’s Comment c’est (1961), by José Emilio Pacheco, Cómo es (1966), stands out as a dazzling and unprecedented landmark in the history of the reception of the Irish author in non-English-speaking countries. In his translation the 27-year-old Mexican poet took the French original version as his main source but, despite its daring quality and the brilliance of the text rendered into Spanish, it had little impact in the cultural atmosphere of its day. In light of Pacheco’s standing in the world of letters as a first-rank critic, translator and poet, it is deemed necessary a reassessment of this unique text. The aim of this article is to analyze Pacheco’s translation of Samuel Beckett’s novel; for this purpose, the historical context and the personal elements that the poet incorporated from his personal background into his version of Comment c’est will be studied in detail. All in all, the final objective of this research is to explain how Beckett is read in Spanish through Pacheco’s version.
Keywords: José Emilio Pacheco; Samuel Beckett; Joaquín Díez-Canedo; translation; contemporary mexican culture